Evaluation of alveolar bone micromorphological changes in experimentally induced periodontal disease rat model by using micro-computer tomography (Micro-CT) - Chew, Xuan-Yee (2018)
Periodontitis is driven by dysbiotic of periodontopathogenic bacteria that may lead to alveolar bone loss.The purpose of this study was to evaluate the alveolar bone micromorphological changes induced by ligature, injection of LPS and combination of ligature-LPS injection in the rat model.Micro-CT scanned data from 72 hemimaxilla of previously induced rats were analysed using Skyscan 1076. Treatment groups consisted of Control, Ligature, Ligature-lipopolysaccharide (Ligature-LPS) and Porphyromonas gingivalis-lipopolysaccharide (Pg-LPS). Each treatment comprised of day 7, 14 and 30. At day 7, both Ligature and Ligature-LPS groups showed significant decrease (p<0.05) in percent bone volume (BV/TV), trabecular thickness (TbTh), and bone mineral density (BMD), but increased in total porosity (PoTot),indicating bone resorption. These changes gradually reduced, and by day 30, they were insignificant (p>0.05) when compared to the Control group. This likely indicate the occurrence of bone remodeling. The Pg-LPS group showed no significant change in all parameters. These results showed that Ligature and Ligature-LPS caused more bone resorption than Pg-LPS in rats.